Procedury kanoniczne zmierzające do stwierdzenia stanu wolnego - Jakubiak, Tomasz (Ius Matrimoniale, 2013)
Statement of non-married status is an action accompanying many office procedures which is something more than regular pre-martial examination. To be accurate in judging someone is not married one has to ask many questions and request both secular and church documents. In majority of cases the thing takes place in diocesan curia or church courts yet there are some situations when it’s the local priest who has to do it. There are circumstances which influence the validity of marriage completed in form other than the one envisaged by the Canon Law Code. One should also consider the evolution of the marriage regulations in the Church. Mistakes made by the priests when stating non-married status of a person can conclude in non-valid or non-licitly reception of this sacrament in the future.